ஈழத்தில் கண்ணகி வழிபாடு - Raguram, S. (Puthiya Aaraichchi, Tamil Nadu, India, 2009)
‘Silappathikaram’ is one of the ancient literature of Tamils widely considered as literature of common men. The messages the literature carries, the portrayal of the life of ancient Tamils that the literature visualizes the civilization, society, politics and economy of the ancient Tamils. These aspects of this literature are particularly important. The modalities of the way of living of ancient Tamil and their connections are well expressed in this literature. The characteristics of Kannaki, the challenges she faced, particularly, the struggles she faced in her life were well admired in Sri Lanka too. These attributes gave the status of Goddess to Kannaki in Sri Lanka. Her life is absorbed as the life of a Goddess. The literature gurus and historians point out her higher status of “chastity”. Looking beyond this portrayal, it cannot be denied the fact that Kannaki’s life reflects the bravery of people in lower economic strata and the belief in fairness. These qualities are the reasons behind the goddess status given to Kannaki. People in this part of the world consider their mothers as goddesses and this belief along with the way of life that is more connected to nature were the features of these people. This kind of worshipping still moves through a rich platform not only in Tamil Nadu but also in Sri Lanka. This article tries to explore the reasons for continuing Kannaki worship in Sri Lanka amidst many reactions and further explores the onset of Kannaki worship, the beliefs of people, changes over time, manipulations and the politics behind these things.